DIAGNOSTIC VALUE OF URIC ACID IN PLEURAL EFFUSION - Saraswati Wulandari Hartono; Nurhayana Sennang; Fitriani Mangarengi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Pleural effusion is excessive pleural fluid accumulation in the aimed pleural cavity, are categorized into exudate and transudate. Light’s criteria (1972) has become a classic criteria to distinguish pleural effusion types. Other criteria were evaluated such as pleural fluid uric acid. The aimed of this study was to analyze the difference of uric acid level between transudate and exudate and to compare it with Light’s criteria. A cross-sectional study was conducted in Clinical Pathology Laboratory of the Dr. Wahidin Sudirohusodo Hospital Makassar in September 2016. Uric acid level of pleural effusion samples was measured by ABX Pentra 400. Statistical analysis used Mann-Whitney U test, significance was indicated if p<0.05. Cut-off, sensitivity and specificity of uric acid used ROC curve. Total subjects were 56 patients, mean age 49.54+13.63 years-old, 31 males (55.4%) and 25 females (44.6%). Most cases were exudative effusion (58.9%) with 19 malignancy cases (33.9%). Uric acid level median was 6.6 mg/dL (3.24-17.50 mg/dL) higher in transudate than exudate 5.01 mg/dL (0.6-9.40 mg/dL) (p=0.001). The cut-off point for pleural fluid uric acid was 5.845 mg/dL, with a sensitivity of 78.3% and specificity of 66.7%. Sensitivity and specificity of Light’s criteria was 97% and 60.9%. There was a significant difference between pleural fluid uric acid level in transudate and exudate, higher in transudate than exudate. Light’s criteria were higher in sensitivity than uric acid, but lower in specificity. Further research is needed with better sampling method to reduce bias.